Natural disasters and labor market outcomes in Mexico - Ivonne Acevedo; Francesca Castellani; Carlos Lopez de la Cerda; Giulia Lotti; Miguel Székely (Inter-American Development Bank (IDB), 2023)
This study examines the relationship between weather emergencies and labor market outcomes in Mexico from 2016 to 2020. Using panel data and a two-way fixed effects estimation, the analysis focuses on storms, floods, wildfires, and landslides. The results show that storms can have significant negative associations with labor market outcomes. When living in municipalities affected by storms, individuals experience 3.5 percent lower wages. Also, storms are associated to a decrease in weekly working hours, while the rest of weatherrelated emergencies do not show significant effects. Furthermore, the probability of employment is negatively and significantly affected by storms, resulting in a 1 percentage point reduction in the likelihood of being employed. Finally, when evaluating dynamic effects, we also find that individuals living in municipalities affected by landslides experience a worsening of labor market outcomes (employment, hours, and wages) in the following quarter.
Keywords: J21; J30; Q54; 330; Climate change; weather emergencies; labor market outcomes; Mexico; storms; floods